Pengaruh Model Student Team Acheivement Division Terhadap Hasil Belajar Penyajian Data Kelas IV Sekolah Dasar - Murisman, Gisti; Arlis, Syamsu (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
This resarch aims to determine the effect of the Student Team Acheivement Division model on the learning outcomes of data presentation in 4th grade of Elementary School. This type of research used quasy eksperiment design. The design used was The Nonequivalent Pretest-postest Control Group Design. The sampling technique used Cluster Random Sampling, which targeted population consisted of several elementary school in Gugus 1 of Lubuk Begalung sub-district. The amount samples of this study are 56 students in 4th grade class of 30 Cengkeh Public Elementary School in Padang City. The instruments used in this research were test based. Data analysis technique used in this research are test-t. This is proven from the acquisition of  thitung = 6,75 > ttabel 2,000 with a real level of  0,05 with dk = 54, which means Ha is accepted and Ho is rejected, it can be concluded that the Student Team Acheivement Divison model has a positive effect on learning outcomes in the data presentation of students 4th grade elementary school.